Structural protein analysis of the polyvalent staphylococcal bacteriophage 812 - Eyer, Ludek; Pantůcek, Roman; Zdráhal, Zbynek; Konecná, Hana; Kaspárek, Petr; Růzicková, Vladislava; Hernychová, Lenka; Preisler, Jan; Doskar, Jirí (Proteomics, 2007)
Phage 812 is a polyvalent phage with a very broad host range in the genus Staphylococcus, which makes it a suitable candidate for phage therapy of staphylococcal infections. This proteomic study, combining the results of both 1-DE and 2-DE followed by PMF, led to the identification of 24 virion proteins. Twenty new proteins, not yet identified by proteome analysis of closely related staphylococcal phages K and G1 were identified using this approach. Fifteen proteins were assigned unambiguously to the head-tail genome module; the remaining nine proteins are encoded by genes of the left or right arms of the phage genome. As expected, the most abundant proteins in the electrophoretic patterns are the major capsid protein, the major tail sheath protein and proteins identical to ORF 50 and ORF 95 of phage K, although their function is only putative. Identification of these 20 new proteins contributes substantially to a detailed characterization of phage virions, knowledge of which is necessary for rational phage therapy.
Keywords: Viral Proteins; proteom; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Staphylococcus Phages; stafylokokové bakteriofágy; Electrophoresis, Polyacrylamide Gel; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Proteome; elektroforéza v polyakrylamidovém gelu; virové proteiny